AI in International Marketing: How Digital Service Firms Standardize and Adapt Marketing Across Borders - Ojala, Arto; Mudiyanse, Thilini; Fraccastoro, Sara; Gabrielsson, Mika (University of Hawaii, 2026)
This study explores how digital service firms apply Artificial Intelligence (AI) in their international marketing efforts. Specifically, we examine how these firms use mechanical, thinking, and feeling AI to standardize, adapt, and personalize their international marketing to international customers. Based on a qualitative multiple-case study, including five Finnish digital service firms, we find that mechanical AI helps different marketing processes related to standardization of marketing mix elements. Thinking AI, commonly used together with mechanical AI, is applied to facilitate the adaptation of product, promotion, and pricing strategies for foreign markets and customers. Feeling AI is applied to personalize the marketing offer based on individual customer needs. Based on these findings, we suggest three propositions that advance research on this topic, and which indicate how each type of AI relates to different stages of the marketing process and various marketing mix elements. This study contributes to research and practice in international marketing by offering a detailed view of how digital service firms apply AI in in their global marketing efforts.
Keywords: Artificial Intelligence (AI); Digital Service Firms; International Marketing; Standardization; Adaptation; Personalization; fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kansainvälinen liiketoiminta|en=International Business|